Synthetic analogues of the nickel-iron hydrogenase family of metalloenzymes - Jones, Graham Joseph (2018)
This thesis describes the syntheses and characterisations of heterobimetallic dithiolate complexes of NiII, PdII and CoII with FeII that derive inspiration from the chemistry and structures of the active sites of the [NiFe] hydrogenase family of metalloenzymes. These studies provide insight into the electronic structures of the Ni-C and Ni-L states of the [NiFe] hydrogenases and the complexes have potential as new catalysts for the production of dihydrogen.